Efficient Communication Using Cluster-To-Cluster Source Route Cooperative Data Transmission Approach in Wireless Ad Hoc Networks - Saravanan MURUGAN; Nithyakalyani SELVARAJAN (Promet (Zagreb))
The wireless ad hoc networks (WANETs) provide a flexible and adaptable infrastructure for transferring data in different environments. It supports multiple description (MD) video transfers, addressing error-prone WANETs, which are becoming increasingly critical as their usage grows. Previous approaches to multicasting MD video in WANETs had significant challenges. Ensuring multimedia streaming quality over WANETs while reducing buffering and traffic are crucial challenges. To overcome the problems, this work proposes a cluster-to-cluster source route cooperative data transmission (C2C-SRCDT) method for packet communication in WANETs. Initially, nodes in cluster formation will be created, and each node’s weights will be evaluated for cluster head (CH) selection. Then, Dijkstra’s transmission routing aware-multiple description video (DTRA-MDV) method estimates the cluster node to select the shortest distance routes between each cluster to send the multiple (image/videos) data. Finally, the time-slot multiple route selection (TSMRS) technique improves throughput and reduces breakage links. C2C-SRCDT reduces buffering and transfers data quality (image/videos) based on network lifetime, bandwidth and transmission time. The proposed simulation is evaluated using various parameters: data delivery ratio, loss, delay, throughput and energy consumption. The proposed system achieves a data delivery ratio of 92%, a delay of 40 sec and a throughput of 91%. These metrics analysed the improvement in video or image quality and traffic to avoid data transfer and transmit the wireless network better than previous approaches.